P477 Patient satisfaction and cost saving analysis of telemedicine in patients with inflammatory bowel disease. (30th January 2023) - Bossa, F; Carparelli, S; Guerra, M; Cocomazzi, F; Martino, G; Annese, M; Nardella, M; Bellucci, N; Gagliardi, R; Terracciano, F; Pacilli, L; Perri, F
Abstract: Background: Crohn's disease (CD) and Ulcerative Colitis (UC) are chronic inflammatory bowel diseases (IBD). Telemedicine (TM) is particularly useful in patients with chronic diseases who need frequent monitoring to achieve therapeutic outcomes and improve their quality of life. We examined the differences in patient satisfaction comparing telemedicine versus traditional in-person visits. We also examined the potential cost savings benefits of utilizing telemedicine. Methods: All consecutive patients with IBD in clinical remission evaluated by Partial Mayo Score (PMS) for UC and Harvey Bradshaw Index (HBI) for CD were considered eligible (PMS<2 or HBI<5). Patients were randomized into two arms: telemedicine or in-person visits after a questionnaire investigating the Information and communication technology (ICT) skills . All patients were asked to respond to an 11-items survey investigating their trust in telemedicine at first in-person visit. Enrolled patients performed after 3 months a telehealth or an in-person visit. All patients answered a standard questionnaire to evaluate the indirect costs of managing their disease. Patients randomized into telemedicine arm answered a specific 28-item survey investigating their degree of satisfaction. Results: We enrolled 30 patients with IBD randomized to telemedicine (n. 22; 11 CD; 13 female; mean age 45 years) or in-person visits (n. 8; 5 CD; 3 female; mean age 52 years). All patients randomized in TM (100 %) showed interest in this new clinical practice and were satisfied of the received information about telemedicine management. No patients thought that telemedicine would have no positive effects on their health status. Regarding demographic data, 6 out of 22 patients randomized to TM (27.2%) lived in a different province than our hospital's and16 patients (72.7%) had high school diploma or degree. All TM patients (100%) were satisfied of the televisit and considered clear the information received during conversation with physician. From a technical point of view, only one patient had problems of connection and three patients needed the support of a caregiver. Eighteen patients (81.8 %) thought that the efficacy of the televisit was equivalent to the in-person visit. Nineteen patients (86.3 %) were convinced that televisit is a tool to be promoted for future clinical practice. Patients randomized to telemedicine had an average saving of 125 €. Data shown are illustrated in the figure 1. Conclusion: In patients with IBD in remission, telemedicine is feasible and effective in the majority of patients. In addition, TM has allowed a significant cost savings without reducing the quality of the health assistance.